The replacement of the tricuspid valve in the removal of the malignant tumor of the right ventricle - Vitovskiy, R. M.; IsaіenkoV. V.; Onishchenko, V. F.; Pishchurin, O. A.; Dyadyun, D. N.; Martyshchenko, I. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The aim of the study was to present an unusual case of secondary lesion of right ventricular (RV) with a malignant neoplasm, the character and size of which was finally recognized during the operation, as well as the peculiarities of surgical treatment of such lesion, which was accompanied by prosthetics of the tricuspid valve. Material and methods. In the National Institute of Cardio-Vascular surgery named N.M. Amosov of the Academy of Medical Sciences of Ukraine since 1970 surgical treatment of 62 patients with various types and localization of malignant heart tumors was performed, which amounted to 6.8% of 912 patients with cardiac tumors. Results. The clinical observation presented by the patient with secondary tumor’s lesion of right ventricular (RV) is of practical interest from the point of view of the complexity of diagnosis, the unusual path of metastasis and the peculiarities of surgical treatment. Conclusions. Metastases in the heart usually arise due to their hematogenous or lymphogenous spread or due to direct invasion. Malignant tumors of the heart can affect not only its walls, but also spread to its valve structures, which requires correction of valvular lesions. It is impossible to exclude the presence of thrombus in the chambers of the heart, considering the violation of hemodynamics associated with the presence of tumors.